Intellectual-personal Potential And The Dynamics Of Student’s state Of Anxiety In Conditions Of Examination Stress - Olefir, Valerii (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2016)
The article discusses the results of a longitudinal study of anxiety state dynamics in students in a situation of examination stress. With the help of a of modeling method the latent changes revealed non-linear form of changes individual trajectories in the state of anxiety. Intellectual and personal potential is considered as a covariate to explain the dispersion at the initial level and the speed of changes in the state of anxiety among students.